Faktor-Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Ibu Hamil - Siti Nafisah; Wiwin Nur Fitriani; Indah Sri Wahyuni (Politeknik Karya Husada, 2025)
Both the mother and the fetus suffer greatly from anemia in pregnant women, a condition that is rather common on a national and international scale. Although the government has provided iron supplements (TTD) and implemented various prevention programs, even in Cianjur Regency, a significant number of pregnant women suffer from anemia. Fetal and neonatal death, as well as other pregnancy problems, are possible outcomes of this illness. For this reason, in order to develop more efficient preventative measures, it is crucial to determine what variables impact the prevalence of anemia. This study aims to determine the factors associated with the incidence of anemia in pregnant women at the Indri Gustiani TPMB. Cianjur Regency in 2025, specifically adherence to iron tablet consumption, knowledge, nutritional status, and family support. Methodology: The study design used was an observational analytic with a cross-sectional approach. The study sample consisted of 60 pregnant women, selected using a total sampling technique. Data were analyzed using the Chi-Square test with a 95% confidence level. The results of the Chi- square statistical test on compliance with Fe tablet consumption (P-value = 0.030), knowledge (P-value = 0.020), nutritional status (P-value = 1.000), and family support (P-value = 1,000). A relationship was found between compliance with Fe tablet consumption and knowledge of the incidence of anemia, and no relationship was found between nutritional status and family on the incidence of anemia. Pregnant women are expected to comply with consuming at least 90 iron tablets, maintain nutritional status with a nutritious diet, increase knowledge through counseling, and involve family support to prevent anemia.